Prognostic value of neutrophil‐to‐lymphocyte ratio in gastric cancer patients treated with immune checkpoint inhibitors: A meta‐analysis - Li‐Li Li; Li‐Sha Pan (Kaohsiung Journal of Medical Sciences, 2023)
Abstract The neutrophil‐to‐lymphocyte ratio (NLR) has been extensively studied in patients with gastric cancer (GC) treated with immune checkpoint inhibitors (ICIs), although the results are controversial. Therefore, we performed the present meta‐analysis to systematically assess the correlation between NLR and prognosis and clinicopathological factors in GC patients undergoing treatment with ICIs. Among the electronic databases, PubMed, Web of Science, Embase, and Cochrane Library were thoroughly searched. To estimate the prognostic value of NLR for progression‐free survival (PFS) and overall survival (OS), hazard ratios (HRs) were calculated, and their 95% confidence intervals were calculated. This meta‐analysis included 10 studies with 830 patients. Based on the pooled data, a high NLR was associated with poor OS in GC patients receiving ICIs (HR = 2.13, 95% confidence interval [CI] = 1.70–2.66, p < 0.001). Elevated NLR was a significant biomarker for worse PFS in GC patients treated with ICIs (HR = 1.74, 95% CI = 1.22–2.48, p = 0.002). There was, however, no significant correlation between NLR and sex, age, and Eastern Cooperative Oncology Group Performance Status (PS) of the ECOG, differentiation, human epidermal growth factor receptor 2 (HER2) status, or PD‐L1 status in GC patients treated with ICIs. High NLR before treatment was associated with poor OS and PFS in GC patients treated with ICIs, according to our meta‐analysis. NLR is an effective biomarker for evaluating the prognosis of GC patients receiving ICIs and provide more valuable information for treatment decisions in the era of immunotherapy for GC.